Women in the Whirlpool: Traversing the Tie-up of Personality and Work-Life Balance of Pakistani Academicians - Salima Shahin; Muhammad Nawaz Baloch; Najia Shaikh; Iqra Ibrahim; Ahsan Ali Abbassi (Faculty of Economic and Business, 2021)
This research strives to explain the impact of personality type on the work-life balance of women academicians. With the positivist paradigm and quantitative approach, this study has been conducted with a survey methodology. Data was collected from 362 women academicians on adopted instruments and analyzed with multiple regression and ANOVA tests. Results revealed a positive effect of agreeableness, extraversion, and openness personality types on work-life balance. Those women academicians who are with agreeableness personalities are more in a capacity to manage their work-life balance. The results also show a difference in managing the work-life balance between those who are single and married, those who belong to a nuclear family, and those who belong to joint or extended families. This study will facilitate them to develop the personality type which has more capacity to manage work-life balance. It will help policymakers to facilitate women academicians to ensure better work-life balance.JEL Classification: M12How to Cite:Shahin, S., Baloch, M. N., Shaikh, N., Ibrahim, I., & Abbassi, A. A. (2021). Women in the Whirlpool: Traversing the Tie-up of Personality and Work-Life Balance of Pakistani Academicians. Etikonomi, 20(2), xx – xx. https://doi.org/10.15408/etk.v20i2.17272.